1997
DOI: 10.1111/j.1460-9568.1997.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical Imaging of Cat Auditory Cortex Cochleotopic Selectivity Evoked by Acute Electrical Stimulation of a Multi‐channel Cochlear Implant

Abstract: We measured reflectance changes by means of optical imaging of intrinsic signals to study the effects of acute electrical cochlear stimulation on the topography of the cat auditory cortex. After single-pulse electrical stimulation at selected sites of a multichannel implant device, we found topographically restricted response areas representing mainly the high-frequency range in AI. Systematic variation of the stimulation pairs and thus of the cochlear frequency sites revealed a systematic and corresponding sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 25 publications
6
21
0
Order By: Relevance
“…Hess and Scheich [1996] describe imaging in the awake Mongolian gerbil; Bakin et al [1996] report data from anesthetized rats and guinea pigs; and Dinse et al [1997] provide data from the cat. The latter study employed electrical stimulation of the cochlea rather than acoustic stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hess and Scheich [1996] describe imaging in the awake Mongolian gerbil; Bakin et al [1996] report data from anesthetized rats and guinea pigs; and Dinse et al [1997] provide data from the cat. The latter study employed electrical stimulation of the cochlea rather than acoustic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Frostig et al, 1990;Gochin et al, 1992]. Only a few preliminary reports have been made on the optical imaging of intrinsic signals from auditory cortex [Bakin et al, 1996;Hess and Scheich 1996;Dinse et al, 1997;Harrison et al, 1997]. We report here on acoustically evoked intrinsic signals arising from cortex.…”
Section: Introductionmentioning
confidence: 99%
“…***p Ͻ 0.001. (Dinse et al, 1997;Raggio and Schreiner, 1999;Bierer and Middlebrooks, 2002;Kral et al, 2006). HS1 includes the expected border between A1 and AAF (Knight, 1977;Phillips and Irvine, 1982;Schreiner and Urbas, 1986).…”
Section: Hearing Controlsmentioning
confidence: 99%
“…[2][3][4]10,13,14,16,17,20,34,39,42,44,49 In these studies investigators have established the credibility of this modality and demonstrated its versatility and potential applications. Highlighting the superior resolution of OIS, Bonhoeffer and Grinvald 4 have characterized radial orientation columns in the cat visual cortex, one of the basic units of visual cortex organization.…”
Section: Optical Mapping In Animal Modelsmentioning
confidence: 99%